KH Muhammad Abduh Pabbajah's Da'wah to the Community in the City of Parepare - Umar, M. Shodiq Asli; Qadaruddin, Muhammad (IAIN Parepare, 2021)
This research discusses the Da'wah of KH Muhammad Abduh Pabbajah to the Community in the City of Parepare. This research attempts to answer the following research problems: 1) What is the strategy of preaching KH Muhammad Abduh Pabbajah to the people in Parepare City?; 2) What is the important theme of KH Muhammad Abduh Pabbajah's preaching to the people in Parepare City?. This research refers to the theories, concepts, and strategies of da'wah introduced by Al-Bayaninu, namely: al-manhaj al-athifi (sentimental strategy); al-manhaj al-`aqli (rational strategy) al-manhaj al-hissi (sensory strategy), and al-manhaj al-fitri (natural strategy). This research uses qualitative research methods based on field research, by applying a phenomenological approach to analyze data and facts found in the research field. This method is used to reveal the meaning of the complexity of the da'wah of KH Muhammad Abduh Pabbajah in the City of Parepare, with the aim that the use of this method can describe the strategies, models, and methods of da'wah from the characters studied holistically and comprehensively. Sources of data in this study were obtained from literature searches, documents, and empirical investigations to obtain a detailed description of field data through purposive interviews with informants. The research that was conducted succeeded in revealing that: 1) The Da'wah Method KH. Muhammad Abduh Pabbajah in the community in Parepare City combined several da'wah methods such as al-manhaj al-athifi (sentimental strategy); al-manhaj al-hissi (sensory strategy), as well as al-manhaj al-fitri (natural strategy) dynamically by paying attention to the situation of the community that is the object of his da'wah. To support the da'wah that was carried out, KH Muhammad Abduh Pabbaja carried out several social activities, such as establishing an Islamic Boarding School Educational Institution, carrying out social activities by becoming the general chairman and secretary general of the Darul Dakwah wal Irsyad (DDI) Executive Board, becoming a State Servant, actively delivering da'wah and filling recitations at the Grand Mosque, making political parties a means of da'wah, as well as conveying da'wah through several writings. 2) The theme and content of KH Muhammad Abduh Pabbajah's da'wah is an invitation to strengthen faith, and instill respect for humans and humanity, in order to maintain the unity of the servant of Allah SWT vertically, and maintain harmonious social relations horizontally. The steps taken by KH Muhammad Abduh Pabbajah in maintaining the balance of the relationship. KH Muhammad Abduh Pabbajah does not spread news that can damage social relations, does clarification (tabayyun) every time he receives news that is not certain to be true, strongly condemns spreaders of false news, always maintains calm, honesty and istiqamah and follows the Sunnah of the Prophet in the treatment of various diseases.